Effect of dialysis dose and membrane flux on hemoglobin cycling in hemodialysis patients. Issue 2 (12th September 2014) - He, Liyu; Fu, Min; Chen, Xian; Liu, Hong; Chen, Xing; Peng, Xiaofei; Liu, Fuyou; Peng, Youming
Abstract Many studies found that hemoglobin (Hb) fluctuation was closely related to the prognosis of the maintenance hemodialysis patients. We investigated the association of factors relating dialysis dose and dialyzer membrane with Hb levels. We undertook a randomized clinical trial in 140 patients undergoing thrice‐weekly dialysis and assigned patients randomly to a standard or high dose of dialysis; Hb level was measured every month for 12 months. In the standard‐dose group, the mean (±SD) urea reduction ratio was 65.1% ± 7.3%, the single‐pool Kt/V was 1.26 ± 0.11, and the equilibrated Kt/V was 1.05 ± 0.09; in the high‐dose group, the values were 73.5% ± 8.7%, 1.68 ± 0.15, and 1.47 ± 0.11, respectively. The standard deviation (SD) and residual SD (liner regression of Hb) values of Hb were significantly higher in the standard‐dose group and low‐flux group. The percentage achievement of target Hb in the high‐dose dialysis group and high‐flux dialyzer group was significantly higher than the standard‐dose group and low‐flux group, respectively. Patients undergoing hemodialysis thrice weekly appear to have benefit from a higher dialysis dose than that recommended by current KDQQI (Kidney Disease Qutcome Quality Initiative) guidelines or from the use of a high‐flux membrane, which is in favor of maintaining stable Hb levels.